KUALITAS SPERMATOZOA KAMBING PERANAKAN ETAWAH PADA KOMBINASI PENGENCER TRIS DAN BEBERAPA JENIS KUNING TELUR - Anisah, Anisah; Riyadhi, Muhammad; Rizal, Muhammad (www.ulm.ac.id, 2024)
The aims of this study was to determine the quality of Etawah crossbreed (PE) spermatozoadiluted with a combination of tris diluent and various types of egg yolks. The researchmethod employed a Completely Randomized Design (CRD) with three treatments and sixreplications, consisting of (P1) 80% tris aminomethane + 20% commercial chicken egg yolk(KTR), (P2) 80% tris aminomethane + 20% local chicken egg yolk (KTK),and (P3) 80% trisaminomethane + 20% quail egg yolk (KTP). The observed daily qualities of PE spermatozoaincluded motility and viability until the motility reached 40%. The results showed that themotility of PE spermatozoa on day 4, P3 (40.00%) was significantly higher (P<0,05) than P1(25,83) and P2 (30,00). The viability of PE spermatozoa showed P3 (45.47%) wassignificantly higher (P<0,05) than P1 (34,65) and P2 (39,93). In conclusion that combinationof tris diluent and various types of egg yolks could maintain the quality of PE spermatozoa onday 3 above 40%, in accordance with the minimum motility requirments for spermatozoa asin SNI 486.3:2014, which is a minimum of 40%, suitable for use in artificial inseminationVol. 3 No. 1, Januari 2024 ISSN: 2442-7012Jurnal Penelitian Peternakan Lahan Basah 19programs. The combination of tris-quail egg yolk diluent better results maintaining thequality of Etawah crossbreed untill on day 4 of storage.